Acercamiento a las Didácticas Implementadas En Los Juegos Teatrales para un Grupo con Diversidad Funcional de Acphes (2018)
So you can get to know the contents of this document must be willing to promise that never stop playing, if you think that you can not make that promise, don't worry, because this document will give you enough reasons to do it safely, the whole is that enjoy, learn, accept, and have fun; because at the end and at the end of that is playing? With the passing of the leaves you will find the relationship that exists between the hide and seek game and the experience of the theatrical process and all leaving within the Colombian Association of parents with children special (ACPHES) where highlights the interest in using the j uegos theatrical as a training strategy within a process theatre to this being an alternative that raises and proposes in the professional work; involving both parties; the learner and the teacher.